Social Media as Tools of Communication and Learning - Sri Rizki, Juni Wati (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The growing digital era brings significant changes in various aspects of life, including education. In today's digital age, social media is essential in multiple aspects of life, including communication and learning. Social media has become part of the lifestyle of today's society and provides many conveniences for humans in communication. This study examines the potential of social media as a communication and learning tool. Concepts such as blended learning, gamification, and e-tutoring will be put forward to help teachers and students optimize the benefits of social media in education. This article will also discuss the challenges of using social media as a school communication and learning tool. This study uses a qualitative method by collecting interviews and observation data from social media users. The results showed that social media could increase communication and learning effectiveness and raise several problems, such as privacy and hoaxes. Therefore, it is essential to properly understand and control social media use as optimally as possible as a communication and learning tool.